2022
DOI: 10.1002/mame.202200442
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Wearable Electrospun Polymeric Piezoelectric Sensors and Energy Harvesters

Abstract: In recent years, wearable sensors and energy harvesters have shown great potential for a wide range of applications in personalized healthcare, robotics, and human-machine interfaces. Among different types of materials used in wearable electronics, piezoelectric materials have gained enormous attention due to their exclusive ability to harvest energy from ambient sources. Piezoelectric materials can be utilized as sensing elements in wearable sensors while harvesting biomechanical energy. Electrospun piezoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 250 publications
0
53
0
Order By: Relevance
“…1,29,38 However, with further increases in BTO content (50, 75, and 100%), the β-phase content decreased to 75.65, 71.94, and 68.34%, respectively, which might result from BTO agglomeration within the nanofibers. 1,17,38 XRD was utilized to examine the crystalline structure of the "dispersed PVDF-TrFE + BTO" nanofibers, as shown in Figure 3c. The crystallinity was determined by taking the ratio of the area under the crystalline peaks to the area under the XRD spectrum, which are displayed in Figure 3d.…”
Section: Measurement Of Piezoelectricitymentioning
confidence: 99%
“…1,29,38 However, with further increases in BTO content (50, 75, and 100%), the β-phase content decreased to 75.65, 71.94, and 68.34%, respectively, which might result from BTO agglomeration within the nanofibers. 1,17,38 XRD was utilized to examine the crystalline structure of the "dispersed PVDF-TrFE + BTO" nanofibers, as shown in Figure 3c. The crystallinity was determined by taking the ratio of the area under the crystalline peaks to the area under the XRD spectrum, which are displayed in Figure 3d.…”
Section: Measurement Of Piezoelectricitymentioning
confidence: 99%
“…Triboelectric sensors typically have high output power, but the design is much more complex and requires a contact separation process involving two surfaces with different charge affinities. 19 Therefore, piezoelectric sensors have attracted much attention for their high sensitivity, simple preparation, and long service life. 20 Piezoelectric materials can generate an electric field while being pressed.…”
Section: Introductionmentioning
confidence: 99%
“…Although piezoelectric and triboelectric sensors are similar in the capability of higher frequency and a broad range of frequency detection, the two types of sensors are quite different in design. Triboelectric sensors typically have high output power, but the design is much more complex and requires a contact separation process involving two surfaces with different charge affinities . Therefore, piezoelectric sensors have attracted much attention for their high sensitivity, simple preparation, and long service life …”
Section: Introductionmentioning
confidence: 99%
“…The obtained piezoelectric PVDF nanober mats were used as exible nanogenerators. [5][6][7] In our previous paper, we investigated the effect of the addition of ionic liquid (IL) 1-ethyl-3-methyl-imidazoliun bis(-triuoromethanesulfonyl) imide ([EMI + ][TFSI − ]), on the crystal structure of PVDF nanobers prepared by ES. 8 From this previous study, we found that the addition of [EMI + ][TFSI − ] promoted electroactive phase formation in PVDF nanobers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electrospinning (ES) is a known as the processing method, where PVDF is transformed to b-phase dominant state simultaneously with the nanober mat form. 5,6 In the ES process, the PVDF solution is ejected from a spinning nozzle and drawn to a metal collector by applying a high voltage. The solvent in the PVDF solution evaporated during the spinning process, resulting in the formation of a nanober mat.…”
Section: Introductionmentioning
confidence: 99%